Design Pattern Instances within Model Driven Development Based on Abstraction, Concretization and Variability - Lacko, Peter; Kajsa, Peter; Návrat, Pavol (Computing and Informatics, 2017)
The main goal of the paper is to present the method of design pattern support based on principles of model driven development: the abstraction, semantics and model transformations. More specifically, the method is based on the principle of suggestion of design pattern instances via the semantic marking of model elements or source code fragments and on the subsequent transformations of this way marked models or source code. Thanks to the continual support of the design patterns at more levels of abstraction and thanks to the transformations between particular model levels and source code, the method is targeted to achieve the applicability in the area of the iterative, incremental and model driven development.